Save Electricity While Complying with Lighting Regulations (Texas Journal of Multidisciplinary Studies, 2021)
Electric lighting - along with other devices for technical equipment of industrial premises, creates comfortable conditions for productive work, the level of illumination significantly affects labor productivity. Therefore, the task of saving electricity in lighting installations should be understood in such a way as to ensure optimal illumination of industrial premises and workplaces and high-quality lighting, and create an environment for the most productive work of workers with a minimum cost of electricity through the correct design and operation of lighting installations.